2019
DOI: 10.1016/j.stemcr.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms, Hallmarks, and Implications of Stem Cell Quiescence

Abstract: Cellular quiescence is a dormant but reversible cellular state in which cell-cycle entry and proliferation are prevented. Recent studies both in vivo and in vitro demonstrate that quiescence is actively maintained through synergistic interactions between intrinsic and extrinsic signals. Subtypes of adult mammalian stem cells can be maintained in this poised, quiescent state, and subsequently reactivated upon tissue injury to restore homeostasis. However, quiescence can become deregulated in pathological settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 105 publications
5
105
0
Order By: Relevance
“…Both pathways are typically active in stem cells, suggesting that multiple small clones may be present and spread throughout the PT and composed of cancer stem cells. This fits well with the cancer stem cell hypothesis, which assumes that small groups of relatively quiescent cancer cells that have acquired stem cell characteristics are present in tumor tissue (1,38,39). Both pathways are generally thought to play an important role in governing metastatic behavior and therapy resistance of cancer stem cells, another hallmark of cancer (1).…”
Section: Within Tumor Heterogeneity Of Signaling Pathway Activitysupporting
confidence: 76%
“…Both pathways are typically active in stem cells, suggesting that multiple small clones may be present and spread throughout the PT and composed of cancer stem cells. This fits well with the cancer stem cell hypothesis, which assumes that small groups of relatively quiescent cancer cells that have acquired stem cell characteristics are present in tumor tissue (1,38,39). Both pathways are generally thought to play an important role in governing metastatic behavior and therapy resistance of cancer stem cells, another hallmark of cancer (1).…”
Section: Within Tumor Heterogeneity Of Signaling Pathway Activitysupporting
confidence: 76%
“…This must entail fundamental considerations for SC well-being such as localizing the SCs at the most well-protected zone (outer limbus) and accrediting SCs with infrequent division. The quiescence state of SCs is believed to be accompanied by reduction in DNA replication, metabolism, gene transcription and protein translation 16 . Notably, these processes were associated with molecular damage due to the production of toxic agents or errors in biosynthesis of macromolecules 79 80 .…”
Section: Discussionmentioning
confidence: 99%
“…noggin) were associated with the exit from quiescence state and the transition into active SC state 18 16 . The bioinformatic analysis of limbal clusters suggests that qLSC engage Pi3K pathway, the BMP-regulated transcription factors Id1/3 63 64 65 , the tumor suppressor gene Trp53 16 , Cyclin D2 68 69 and the Wnt inhibitor Srf1 86 , all of which were linked with growth arrest. Of interest, aLSCs were enriched for TNF, WNT and Ap-1 pathways (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For the signaling pathways we enriched TP53 regulates metabolic genes, aging, regulation of epidermis development, transcriptional regulation by TP53, interleukin-10 signaling, NABA secreted factors, cytokine-mediated signaling pathway, and negative regulation of cell proliferation; in particular, the upstream gene of the P53 signaling pathway, Tp53, predicts apoptosis of hair follicles [38,39]. In addition, we inferred that inner bulge cells had earlier expression patterns of the marker genes Krt6a [40] and Krt10 [41], and developed earlier than outer bulge cells, about which there have been few reports [42]. On the whole, our study revealed the function of intermediate cells 10 in promoting the growth of cashmere and maintaining its attachment to the skin.…”
Section: Dp Cell Ultimate Fate: Hair Follicle Development and New Casmentioning
confidence: 79%